A study of the charge structure and energy utilisation in a Stirred Media Detritor using DEM-SPH - Ndimande, Conrad B (Department of Chemical Engineering, 2023)
The Stirred Media Detritor, (SMD), is a grinding device used for fine and ultra-fine grinding applications in mineral processing. The SMD has a vertically orientated shell that supports a shaft, with protruding impeller arms for agitating the charge. There is currently limited understanding of charge structure and motion in the SMD, particularly the interaction of the media and the slurry. Additionally, the number of arms and their arrangement on the shaft, are important aspects of the impeller that determine flow, energy consumption and grinding efficiency. Impeller geometry choices affect these characteristics of the process. This work focuses on studying the flow of grinding media and slurry for the industrial scale SMD 1100- E. This information is used to explore charge dynamics and energy utilisation in the SMD. To investigate the effect of impeller arm configuration on the operational behaviour of the SMD, the commercially available impeller configuration of the industrial scale SMD 335-E is used as the base case. Mill charge dynamics, transport and mixing, patterns of energy absorption on the mill surfaces are examined for the base case and compared to three different impeller arm arrangements. A two-way transient coupled Discrete Element Method (DEM) and Smoothed Particle Hydrodynamics model is used to achieve this. The ceramic grinding media is represented by the DEM component of the model, which is fully resolved, while the slurry (water and fine particles) is represented by the Smoothed Particle Hydrodynamics (SPH) model. The focus is on steady state operation therefore discharge from and feed into the mill are omitted. A nominal media size of 8 mm is used. The rotational action of the impeller forces the charge to the mill wall creating vortex centred on the mill shaft. The vortex is conical with a large diameter at the bottom, which decrease towards the bottom of the mill. Abrasion is found to be the dominant breakage mechanism in the SMD. Mixing behaviour is complex with media transfer past layers of impeller arms being influenced by the fall distance of media between impeller arm encounters.